Intelligent Sensing Technologies for Nondestructive Evaluation - Pedro Manuel Brito da Silva Girão (Ed.) (MDPI - Multidisciplinary Digital Publishing Institute, 2018)
Nondestructive evaluation (NDE) sensing has progressed significantly in the past few years. In particular, smart sensors play an increasingly important role in structural damage detection. There is growing progress in the performance of strategic sensors, such as piezoelectric sensors, as well as noncontact sensors, such as air-coupled transducers, magnetic flux leakage sensors and pulsed laser ultrasonic propagation applications. The most progress has been made in the development of application software for all technologies. We are now able to enhance damage resolutions and then focus on damage visualization in many applications. This Special Issue highlights advances in the development, testing, and use of damage visualization tools for smart sensor-based nondestructive evaluations. Topics covered include: • New developments in smart sensing-based nondestructive evaluations • Magnetic flux leakage sensors • Laser scanning-based ultrasonic propagation sensors • Piezoelectric sensors • Air-coupled transducers • Damage detection and visualization